Analisis Ajen Atikan Dina Novel Pelesir Ka Basisir Karya Risnawati - Triana, Rio Agus; Rachman, Fahmi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to describe the content of the story, structure, and ajen atikan in the novel Pelesir ka Basisir by Risnawati with an analysis of the structure and ajen atikan. This research is qualitative research using a qualitative descriptive method. The existing research technique used is the literature review technique. The instrument used in this study is a data card. The data analysis technique used in this study is using content analysis techniques. The results of this research are the first content of the story in the novel Pelesir ka Basisir. Second, the story structure in the novel. The theme in travel; The plot used in this novel is a forward plot; There are 26 perpetrators in this novel. Of the 26 perpetrators, the 6 main perpetrators were their children and uncles, including Zahra, Ghifa, Iqbal, Pio, Galih, and Mang Oboy. There were 20 additional perpetrators including Emah, Apa, Mang Parman, Aki Haji, Umi Haji, Ua Sri, Ua Wawan, Bi Esih, Umi Ooy, Mang Didin, Ua Didi, Ua Lilis, Ua Jujun, Bi Icih, Bi Icah, Pa Asep, Tukik Officer, Bule, Villa Security Guard, and Mang Sapri. The settings in this novel include 11 time descriptions, 39 place settings, 8 social settings. Katilu, the ajen atikan contained in the novel, there are 5 atikan manusa ka Gusti, atikan manusa ka personal self, atikan manusa ka manusa sejen, atikan manusa ka alam, atikan manusa ka nature